Sex Roles and the School - Delamont, Sara (Routledge Library Editions: Education, 1990)
Schools reflect the society which surrounds them but they must also be agents of change. The last few decades have seen an explosion of research on gender and education and, in this volume the author examines in a rigorous but highly accessible way, new research findings and new strategies for change, continuing to argue that both sexes lose out from sexist schooling.